PELATIHAN PENGGUNAAN STRENGTHS AND DIFFICULTIES QUESTIONNAIRE PADA GURU BIMBINGAN KONSELING UNTUK DETEKSI DINI GANGGUAN EMOSI DAN PERILAKU PADA REMAJA - Liza, Rini Gusya; Yanis, Amel; Yaunin, Yaslinda; Ashal, Taufik; Sauma, Eldi; Marni, Trisna; Syafwan, Ridho Akbar; Yuliandi, Rozi; Ariadi, Ariadi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Emotional and behavioral disorders in adolescents are mental health conditions that significantly affect adolescents' feelings, thoughts, and behavior. These disorders can interfere with school, family life, friendships, and overall development. The purpose of this activity is to provide training on the use of the Strengths and Difficulties Questionnaire (SDQ) to guidance and counseling teachers for the early detection of emotional and behavioral disorders in adolescents. The activity method is to provide training on the use of the SDQ questionnaire to guidance and counseling teachers in high schools throughout Padang City. The results after the training was given to 35 guidance and counseling teachers showed an increase in the average knowledge score before and after. The results of the facilitator's evaluation of the participants' skills were generally very good, while the participants' evaluation of the training was generally very satisfactory. It is hoped that this training will facilitate guidance and counseling teachers in the early detection of emotional and behavioral disorders